THE SIGNIFICANCE OF SLEEP IN GLUCOSE METABOLISM REGULATION – THE ROLE OF CIRCADIAN RHYTHM DISRUPTIONS IN TYPE 2 DIABETES DEVELOPMENT: A NARRATIVE REVIEW - Klaudia Wojciech; Anastasiia Holoborodko; Ewa Wieczorkiewicz; Patrycja Stępińska; Eliza Garbacz; Agnieszka Pocheć; Bartosz Lautenbach; Dariusz Nędza; Anhelina Loputs; Wiktoria Błaszczyk (International Journal of Innovative Technologies in Social Science, 2026)
Background: Sleep and circadian rhythm disturbances constitute modifiable risk factors for type 2 diabetes mellitus (T2DM). Meta-analytic evidence demonstrates that short sleep duration (